Nivolumab and dinutuximab beta in two patients with refractory neuroblastoma. Issue 1 (15th May 2020) - Ehlert, Karoline; Hansjuergens, Ina; Zinke, Andreas; Otto, Sylke; Siebert, Nikolai; Henze, Guenter; Lode, Holger
Abstract : Background: Neuroblastoma (NB) is the most frequent extracranial solid tumor in children. More than 50% of patients present with widespread (stage M) or refractory disease. In these patients, event-free and overall survival was improved by the addition of the anti-disialoganglioside antibody dinutuximab beta (DB) following multimodal conventional therapy. However, the prognosis of patients with refractory/relapsed NB remains poor. In the past decade, immunotherapy approaches with checkpoint inhibitors were approved for patients with certain malignant diseases such as melanoma or Hodgkin lymphoma. In preclinical models, DB resulted in an upregulation of the programmed cell death protein 1 (PD-1) checkpoint in NB cell lines and a combined treatment of DB with a murine anti-PD-1 checkpoint inhibitor showed a synergistic effect in a NB mouse model. Case presentations: Two patients were admitted with refractory metastatic NB. In the 4-year-old girl, NB was diagnosed in 2013. She completed her first-line therapy with a first remission in 2015, but suffered a relapse in 2017. Treatment with chemotherapy and DB resulted in progressive disease after transient improvement. In the 17-year-old young man, NB was first diagnosed in April 2010. After two local relapses in 2011 and 2014, a metastatic relapse and a large abdominal tumor bulk were found in 2018. Despite transient improvement with multimodal therapy, progressive metastatic disease was observed in May 2019. Both patients had a satisfactory quality of life. Therefore, treatment with DB and nivolumab was performed—in the girl from October 2018 until August 2019, in the young man since June 2019. Tolerance to treatment was excellent. The girl continues to be in complete remission 6 months after therapy was stopped. In the young man, the soft tissue lesions disappeared completely, the skeletal lesions regressed substantially after 9 months of his still ongoing treatment. Conclusions: The combination of DB with the checkpoint inhibitor nivolumab led to complete and a very good partial remission in two patients with relapsed/refractory NB. Prospective trials are warranted to clarify the role of this novel approach in a larger number of patients.